PERENCANAAN PENGGANTIAN JEMBATAN TINJOMOYO KOTA SEMARANG - Rani Wijayanti; Wisnu Dwi Sampurno; Moga Narayudha; Indrastono Dwi Atmanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Along with growth of density of traffic getting through joint streets of Ngadirojo Biting so government of Province Central Java of has a plan to innovate Bridge of Mider III . This Matter because of the Bridge have passed plan and also Wonogiri is area which is expanding and the position of strategic that is connecting Sub-Province of Wonogiri Central Java with Sub-Province of Ponorogo Java East. Replacment of Mider III Bridge to be build this is prestressed-concrete Bridge with length 50 meters. This bridge consist of two unfolding limited by one pillar and two abutment. The width of bridge is 9,7 m that consists of 2 traffic lanes, 3,5 m width of each lane and there are pavement 1 m width in the right and left side of the bridge. For upper structure, there are reinforced concrete for floor bridge, and the girders uses 10 prestreesed concrete type I height (H) 1600 mm. For under structure consists of reinforced concrete abutment with contrafort, and for pillar, it is made from reinforced concrete with rectangle shape 3 m x 3 m, and for foundations its used The Foundation using the sinks foundation with diameter 3,5 m for abutment and 5 m for pillar , the depth of the sinks foundation for abutment is 5 m and the depth of the sinks foundation for pillar is 7 m. On the design of this bridge,Mider III is planned also connection way between bridge and ring road way which is called oprit are also designed. Each way has length 125 m and it is same on Wonogiri destination and Ponorogo destination. This connection way uses flexible pavement with laston thick 100 mm, base course foundation with class A aggregate thick 200 mm, upper course foundation with sirtu class B thick 400 mm. Based on the bill of quantity the design of Tambakboyo bridge needs Rp 5.063.827.000,00 (Five Billion Sixty Three Million Eight Hundreds twenty seven Thousand rupiah ) and PPN 10 % Rp 506.382.700,00 (Five Hundreds Six Million Three Hundred eighty two Thousands Seven Hundred Rupiah). While this project can be finished on 34 weeks.